Serological Survey of Rickettsia japonica Infection in Dogs and Cats in Japan - Tabuchi, Masae (American Society for Microbiology (ASM), 2007)
Antibodies against Rickettsia japonica in 20 of 1,207 dogs and 5 of 584 cats in Japan were detected using immunofluorescence. Some antibody-positive animals were detected in Niigata and Kagawa Prefectures, areas in which Japanese spotted fever in human patients has never been identified. Some animals were positive for antibodies against other new Rickettsia species.